The Effects of Money Attitudes and Financial Satisfaction Among Malaysians On Demand For Family Takaful - Mubarokah Binti Bunyamin
Family takaful business is reported to perform only 14.61 percent of the market penetration rate in 2016. This performance is rated as below its potential market as compared to its conventional counterpart - life insurance. This performance is subjected to debate since family takaful possessing Syariah compliant characteristics and being geared towards a Malaysian Muslim majority populace. Findings from previous studies agreed that psychological factors are among the factors that influence customers' demand for family takaful. This study aims to identify psychological factors of money attitudes and levels of financial satisfaction among Malaysians. Money attitudes and level of financial satisfaction are proven from previous studies to have impact on one's financial planning and decision. Therefore, this study also intends to investigate the effects of these factors with respondents' demand for family takaful as a financial planning instrument. A survey was conducted for this purpose using self-administered and printed questionnaires. The survey involves 200 Malaysian career respondents around Melaka, Nilai, Putrajaya, Cybe rjaya, and Kuala Lumpur. Data was collected within a four month period using convenience sampling. The questionnaire consists of 63 questions, 10 of which focus on demography. The questionnaire uses Klontz-MSI to investigate money attitude dimensions and Morgan's single item question to identify levels of financial satisfaction. Regression used one-way ANOVA for hypotheses testing. Results show that all hypotheses proposed are rejected. All dimensions in money attitudes, money avoidance, money worship, money status, and money vigilance as well as one's level of financial satisfaction do not affect his or her demand for family takaful.